Periodic Genotype Shifts in Clinically Prevalent Mycoplasma pneumoniae Strains in Japan - Kenri, Tsuyoshi; Suzuki, Masato; Sekizuka, Tsuyoshi; Ohya, Hitomi; Oda, Yoichiro; Yamazaki, Tsutomu; Fujii, Hiroyuki; Hashimoto, Toru; Nakajima, Hiroshi; Katsukawa, Chihiro; Kuroda, Makoto; Shibayama, Keigo (Frontiers in Cellular and Infection Microbiology, 2020)
Nationwide increases in M. pneumoniae pneumonia cases in Japan were reported in 2011, 2012, 2015, and 2016. In this study, we performed a genotyping analysis on 554 Mycoplasma pneumoniae strains isolated in 4 areas in Japan (Kanagawa, Okayama, Osaka, and Saitama) between 2006 and 2019. More than 80% of the strains isolated in 2011 and 2012 harbored type 1 p1 gene; however, type 2 lineage strains increased in 2015 and 2016 and dominated after 2017. These findings suggested that a shift in the prevalent genotype of M. pneumoniae clinical strains occurred recently in Japan. The majority of the type 1 lineage strains isolated after 2010 harbored macrolide-resistance mutations in their 23S rRNA gene, whereas most type 2 lineage strains had no such mutations. Consequently, the increase in type 2 lineage strains in Japan has reduced the macrolide resistance rate of clinical M. pneumoniae strains. We identified M. pneumoniae strains carrying a novel variant type 1 p1 gene, and we classified it as type 1b. We sequenced the genomes of 81 Japanese M. pneumoniae strains and compared them with 156 M. pneumoniae genomes deposited in public databases to provide insights into the interpretation of M. pneumoniae genotyping methods, including p1 typing, multiple-locus variable-number tandem repeat analysis (MLVA), multi-locus sequence typing (MLST), and typing by 8 single-nucleotide polymorphism markers (SNP-8). As expected, p1 typing, MLST, and SNP-8 results exhibited good correlation with whole-genome SNP analysis results in terms of phylogenetic relationships; however, MLVA typing results were less comparable to those of the other methods. MLVA may be useful for the discrimination of strains derived from a single outbreak within a limited area; however, is not reliable for classification of strains collected from distantly separated areas at different time points. This study showed the usefulness of genome-based comparison of M. pneumoniae for molecular epidemiology. Genome sequencing of more strains will improve our understanding of global propagation routes of this pathogen and evolutionary aspects of M. pneumoniae strains.